Key Elements of Green Chemistry - Lucia, Lucian (Open textbook library., 2018)
Green chemistry, in addition to being a science, it is also a philosophy and nearly a religion. Attendance at American Chemical Society Green Chemistry & Engineering Conferences will instill such an ideal into any attendant because of the nearly universal appeal and possibilities in this novel approach to radicalizing the business of doing science and engineering.